English Phonetics and Phonology Paperback with Audio CDs - Roach, Peter ([S.l.] : Cambridge University Press, 2009)
Since the publication of the first edition in 1983, this course has established itself as the most practical, comprehensive text in the field and become widely used in many parts of the world in universities and other institutions of higher education. This new edition takes into account recent developments in the teaching of phonology. It includes updated references, fuller coverage of intonation, and a new chapter on different varieties of English with illustrative recorded material. At the end of each chapter in the book there are notes giving information on further reading, discussion of the more challenging issues, written exercises and, where appropriate, suggestions for teachers. In addition the audio CDs include recorded exercises for every chapter which are particularly helpful for non-native speakers. A full answer key is available at the back of the book. Additional exercises and other supporting material are available online.
Keywords: English phonetics